The influence of phenotypes of moor frog (Rana arvalis) to the sizes of pinworms with the different locations (Experimental biology, 2015)
In the article the influence of the picture on the back of moor frog (Rana arvalis) to the sizes of pinworms with the intestine and lung locations was considered. Maximal sizes of nematodes Rhabdias bufonis were observed most often in the frogs with strokes and spots, sometimes – with the intermediate phenotype, minimal – always in the hosts with the straight uninterrupted stripes on the back. For Oswaldocruzia fi liformis in the most cases the arrange of largest nematodes’ sizes to the frogs with uninterrupted along stripes, minimal sizes – to the phenotype with the strokes and spots was recorded. It is probability, that uninterrupted strokes are the basic phenotype, interrupted (until spots and strokes) – mutant variations. We can proposed, that the restoration of the host’s organism after the parasitizing of blood-feeding worms is more successful in the mutant specimens with higher rates of metabolism, whereas the intestine helminthes use the hosts with basic phenotype and economic metabolism more rationally.
Keywords: helminthes hemipopulation; phenotype of fair frog; abundance of nematodes; Oswaldocruzia filiformis